Bowel Preparation With Polyethylene Glycol 3350 or Fasting Only Before Peroral Single-balloon Enteroscopy: A Randomized European Multicenter Trial. Issue 2 (February 2020) - Lenze, Frank; Nowacki, Tobias; Schöppner, Sabine; Ullerich, Hansjörg; Bettenworth, Dominik; Soriani, Paola; Gabbani, Tommaso; Mirante, Vincenzo G.; Domagk, Dirk; Manno, Mauro; Lenz, Philipp
Abstract : Background: Although bowel preparation before colonoscopy and capsule endoscopy is widely evaluated and usually follows established guidelines, a standard preparation regime for peroral small bowel enteroscopy is yet to be defined. The aim of the present study was to compare small bowel preparation with polyethylene glycol (PEG) and "fasting only" (FO) before peroral single-balloon enteroscopy (SBE). Study: We compared small bowel preparation with PEG versus "FO" for peroral SBE in a randomized European multicenter trial. Patients' and procedural characteristics were documented and carefully analyzed. Primary endpoint was the oral intubation depth of the small bowel. A modified Boston preparation scale was used to assess bowel cleansing as a secondary endpoint. Results: In total, 43 patients were enrolled in this study (FO group: n=25; PEG group: n=18). In both groups, patients' characteristics were comparable. The indications for oral enteroscopy were equally distributed in both groups ( P =0.894). The oral intubation depth was significantly higher in the PEG versus the FO group (261±87 vs. 203±66 cm; P =0.019; mean±SD), while the quality of bowel preparation was equally sufficient in both groups [complete visualization of the mucosa (Boston preparation scale) 83% versus 76% ( P =1.000)]. Conclusions: Small bowel preparation with PEG for SBE yields significantly deeper intubation as compared with "FO" preparation. As patient comfort and safety was similar in both groups, PEG preparation might be favored, especially if deep intubation of the small bowel is desired. For patients requiring visualization of the proximal jejunum, a FO preparation seems to be sufficient.